2010
DOI: 10.1177/154193121005402710
|View full text |Cite
|
Sign up to set email alerts
|

Training Effectiveness of Wearable and Desktop Simulator Interfaces

Abstract: The availability of increasingly advanced simulation interfaces has led researchers to question whether these newer interfaces provide a more effective means of providing simulation-based training. An empirical evaluation was conducted comparing the knowledge gained from training with three different systems: narrated computer animations (Flash videos) that are currently in use in the U.S. Army, an interactive virtual environment presented on a standard desktop PC, and the same virtual environment presented on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
2
9
1
Order By: Relevance
“…This experiment validates prior research (Taylor & Barnett, 2011) which found no training advantage from the use of a wearable simulator over a desktop computer when training basic field maneuvers. The current experiment tested the wearable and desktop interfaces for their ability to train more complex procedural skills and again found no appreciable difference between the wearable and desktop in their training capabilities.…”
Section: Comparing Wearable and Desktop Simulation Interfacessupporting
confidence: 88%
See 4 more Smart Citations
“…This experiment validates prior research (Taylor & Barnett, 2011) which found no training advantage from the use of a wearable simulator over a desktop computer when training basic field maneuvers. The current experiment tested the wearable and desktop interfaces for their ability to train more complex procedural skills and again found no appreciable difference between the wearable and desktop in their training capabilities.…”
Section: Comparing Wearable and Desktop Simulation Interfacessupporting
confidence: 88%
“…However, the results of this experiment suggest that being able to perform these movements seems to have little influence on learning procedural skills. Results from the previous experiment (Taylor & Barnett, 2011) indicated that the features of the wearable interface also have little influence on learning cognitive skills, at least no more than the desktop interface or training videos. If the assumption that the improvement in mission completion time was due to the simulator groups learning psychomotor skills, then it is clear the wearable simulator's use of natural movements does not transfer to live performance.…”
Section: Simulator Trainingmentioning
confidence: 88%
See 3 more Smart Citations